2009
DOI: 10.1021/jf9022367
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Allergy: Detection of IgE-Binding Lipid Transfer Proteins in Tomato Derivatives and in Fresh Tomato Peel, Pulp, and Seeds

Abstract: There is an increasing consumption of tomatoes worldwide: fresh in salads, cooked in household sauces, or industrially processed. Although many tomato allergens have been identified, there is no information in the literature on the allergenic components found in commercial tomato products. The primary aim of the study was to evaluate the allergenic profile of commercial tomato products by skin prick tests (SPTs) and IgE/immunoblotting in tomato-allergic subjects. The secondary end point was the study of the Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 24 publications
2
38
0
1
Order By: Relevance
“…The analysis was carried out on single-strand cDNA synthesized on RNA extracted from San Marzano tomato fruits, starting with the oligo-dT primer. RNA was purified from complete fruit since the presence of allergenic LTPs in tomato pulp has also been reported (Pravettoni et al, 2009). Double-stranded cDNA molecules were obtained by PCR using oligonucleotides TomSM-22_F (or TomSM-21_F) and the anchor primer (AP).…”
Section: Race Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was carried out on single-strand cDNA synthesized on RNA extracted from San Marzano tomato fruits, starting with the oligo-dT primer. RNA was purified from complete fruit since the presence of allergenic LTPs in tomato pulp has also been reported (Pravettoni et al, 2009). Double-stranded cDNA molecules were obtained by PCR using oligonucleotides TomSM-22_F (or TomSM-21_F) and the anchor primer (AP).…”
Section: Race Analysismentioning
confidence: 99%
“…Indeed, the Sola I 3 allergen is reported as corresponding to an LTP protein (P93224) for which allergenicity has not been investigated (Plant et al, 1991). Allergenicity of other tomato 9 kDa LTP isoforms from different tomato varieties, has been verified (Bencivenni et al, 2014;Le et al, 2006;Pravettoni et al, 2009), but sequence and structural data are still missing.…”
Section: Introductionmentioning
confidence: 99%
“…The common observation that some people exhibit allergic symptoms to raw tomato is important to the food industry considering the increasing consumption of raw tomatoes in salads worldwide. Ten out of 17 patients (25%) reported allergic reactions to cooked tomatoes; in immunoblotting tests, their sera reacted only to lipid transfer protein (LTP) (Pravettoni et al, 2009). In fresh tomato, different LTP isoforms are present and allergenic.…”
Section: Solanaceae Species Causing Allergic Contact Dermatitismentioning
confidence: 99%
“…In fact, it was shown that LTPs retain their allergenic activity during processing; thus, even cooked food, fruit juices, jams, and fermented drinks still display IgE-binding activity [22‱‱]. It is noteworthy that LTPs were the only detectable allergens in different commercial tomato products [45]. In addition, several studies have demonstrated the resistance of LTPs to proteolysis by pepsin [22‱‱], while gastric and duodenal digestion was assessed in detail for Vit v 1 [46].…”
Section: Symptoms Upon Ingestionmentioning
confidence: 99%